2024
DOI: 10.1002/smo.20230022
|View full text |Cite
|
Sign up to set email alerts
|

Electron‐withdrawing inductive effects enhanced strategy for protein thiol sensing and blocking agent design

Liangwei Zhang,
Shudi Liu,
Xia Zhang
et al.

Abstract: It is a great challenge to discover novel chemical reactions suitable for biological analysis in a living system. The development of novel protein thiol blocking agents is a crucial need for exploring protein thiol functions in protein refolding, signal transduction, and redox regulation. We are always keen on seeking novel chemical reactions applied to endogenous biological macromolecules or protein thiol sensing, blocking, and labeling. In the present work, we have successfully developed a novel agent to blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In addition, we further investigated the probe HBT-Zn-red incubated with 6-OHDA under a shorter time (Figure S18), the fluorescent signal also showed a certain diminishment. Zinc ion loss may be ascribed to the reason that the sulfhydryl group of protein was destroyed by oxidative stress in the PD model, thereby leading to a loss of binding ability with zinc . All the results suggested that zinc ion was greatly reduced in the PD model by 6-OHDA stimuli, further indicating zinc ion plays an important role in maintaining redox balances.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition, we further investigated the probe HBT-Zn-red incubated with 6-OHDA under a shorter time (Figure S18), the fluorescent signal also showed a certain diminishment. Zinc ion loss may be ascribed to the reason that the sulfhydryl group of protein was destroyed by oxidative stress in the PD model, thereby leading to a loss of binding ability with zinc . All the results suggested that zinc ion was greatly reduced in the PD model by 6-OHDA stimuli, further indicating zinc ion plays an important role in maintaining redox balances.…”
Section: Resultsmentioning
confidence: 90%
“…Zinc ion loss may be ascribed to the reason that the sulfhydryl group of protein was destroyed by oxidative stress in the PD model, thereby leading to a loss of binding ability with zinc. 42 All the results suggested that zinc ion was greatly reduced in the PD model by 6-OHDA stimuli, further indicating zinc ion plays an important role in maintaining redox balances.…”
Section: ■ Experimental Sectionmentioning
confidence: 89%